Modern Money Theory and interrelations between the treasury and the central bank: The case of the United States - Éric Tymoigne (Levy Economics Institute of Bard College, 2014)
One of the main contributions of Modern Money Theory (MMT) has been to explain why monetarily sovereign governments have a very flexible policy space that is unconstrained by hard financial limits. Not only can they issue their own currency to pay public debt denominated in their own currency, but they can also easily bypass any self-imposed constraint on budgetary operations. Through a detailed analysis of the institutions and practices surrounding the fiscal and monetary operations of the treasury and central bank of the United States, the eurozone, and Australia, MMT has provided institutional and theoretical insights into the inner workings of economies with monetarily sovereign and nonsovereign governments. The paper shows that the previous theoretical conclusions of MMT can be illustrated by providing further evidence of the interconnectedness of the treasury and the central bank in the United States.
Keywords: E02; E42; E52; E62; 330; Modern Money Theory; Monetary Policy; Fiscal Policy